The impact of urban polycentralization and scale expansion on economic efficiency: evidence from Chinese cities - Jiang, Xinyang; Wei, Siyi; Yi, Chen; Liu, Siyu; Yang, Bo; Wu, Yao (Frontiers in Environmental Science, 2025)
IntroductionThis study investigates the effects of urban polycentricity and city size on total factor productivity (TFP) in Chinese cities.MethodsUsing high-resolution population distribution data from Landscan and applying instrumental variable (IV) estimation to address endogeneity concerns, we construct a novel measure of urban polycentricity.ResultsOur findings show that while expanding city size enhances TFP through increased economies of scale, greater urban polycentricity negatively affects productivity by weakening agglomeration economies and innovation spillovers.DiscussionThe analysis suggests that polycentricity reduces the concentration of economic activities, which hampers knowledge diffusion and innovation, leading to lower productivity. Additionally, we identify the optimal city size for maximizing TFP, where excessive urban growth beyond a certain point becomes counterproductive.